What You Ask is What You Get: Willingness-to-Pay for a QALY in Germany - Marlies Ahlert; Friedrich Breyer; Lars Schwettmann (Center for Economic Studies and ifo Institute (CESifo), 2013)
We report results of a survey of a representative sample of the German population in which respondents were asked in various scenarios for their willingness-to-pay (WTP) for a gain of one quality-adjusted life year. While one version of the survey exactly copied the setting (online survey) and the questionnaire used in the EuroVaQ project, in the second version the hypothetical nature of the questions was emphasized more strongly, and the survey was conducted as a computer-assisted personal interview. The results show that the average and median WTP responses differed between scenarios but, overall, became considerably larger in the second version.
Keywords: I18; 330; willingness to pay; QALY; survey; Germany; EuroVaQ